Trends and socio‐economic disparities in catastrophic health expenditure and health impoverishment in China: 2010 to 2016. Issue 2 (27th November 2019) - Zhao, Yang; Oldenburg, Brian; Mahal, Ajay; Lin, Yaqi; Tang, Shenglan; Liu, Xiaoyun
Abstract: Objectives: To investigate trends and socio‐economic disparities in the catastrophic health expenditure (CHE) and health impoverishment in China after major reform of the health system and to examine the impacts of the chronic disease on CHE and impoverishment. Methods: We obtained data from four rounds of the China Family Panel Studies 2010–2016, with a sample size of 14 960 households. We defined CHE as the point at which annual household health payments exceeded 40% of annual capacity to pay. Impoverishment is measured by the 1.90 per day poverty line. Multivariate logistic regression models were performed to identify impacts of the family member with chronic disease on CHE and impoverishment. Results: Between 2010 and 2016, the incidence of CHE in China decreased from 19.37% to 15.11% and from 7.39% to 5.14% for health impoverishment; however, the decrease in level of impoverishment was less in rural areas (from 6.16% down to 3.03%) than in urban areas (from 8.46% down to 7.81%). The gap between impoverishment rates across the income quartiles is growing. Multivariable analysis showed that households with two or more members suffering chronic diseases were significantly more likely to incur CHE (aOR: 2.46, 95% CI: 1.93–3.13) and impoverishment (aOR: 2.66, 95% CI: 1.87–3.78) than households with no members suffering chronic diseases, after adjusting for sociodemographic covariates. Conclusions: Important advances have been made in achieving greater financial protection for Chinese citizens. Nevertheless, greater attention to the poor households with chronic disease members is needed. Policymakers in China should focus on optimising integrated rural–urban health insurance by expanding the current benefit packages and strengthening poverty alleviation efforts. Abstract : Objectifs: Investiguer les tendances et les disparités socioéconomiques dans les dépenses de santé catastrophiques (DSC) et l'appauvrissement de la santé en Chine après une réforme majeure du système de santé et examiner les impacts de la maladie chronique sur les DSC et l'appauvrissement. Méthodes: Nous avons obtenu des données provenant de quatre séries des Etudes du Panel de la Famille de Chine 2010–2016 sur un échantillon de 14.960 ménages. Nous avons défini la DSC comme le point à partir duquel les paiements annuels pour la santé des ménages dépassaient 40% de la capacité de paiement annuelle. L'appauvrissement a été mesuré par le seuil de pauvreté de 1, 90 par jour. Des modèles de régression logistique multivariée ont été effectués pour identifier les impacts du membre de la famille atteint d'une maladie chronique sur la DSC et l'appauvrissement. Résultats: Entre 2010 et 2016, l'incidence des DSC en Chine est passée de 19, 37% à 15, 11% et de 7, 39% à 5, 14% pour l'appauvrissement de la santé. Cependant, la baisse du niveau d'appauvrissement a été moindre dans les zones rurales (de 8, 46% à 7, 81%) que dans les zones urbaines (de 6, 16% à 3, 03%). L'écart entre les taux d'appauvrissement dans les quartiles de revenu se creuse. L'analyse multivariée a montré que les ménages comptant deux membres ou plus souffrant de maladies chroniques étaient significativement plus susceptibles de subir une DSC (aOR: 2, 46; IC95%: 1, 93–3, 13) et un appauvrissement (aOR: 2, 66 ; IC95%: 1, 87–3, 78) que les ménages sans membres souffrant de maladies chroniques, après ajustement pour les covariables sociodémographiques. Conclusions: D'importants progrès ont été réalisés pour assurer une meilleure protection financière des citoyens chinois. Néanmoins, une plus grande attention aux ménages pauvres comptant des membres atteints de maladies chroniques reste nécessaire. Les décideurs de politiques en Chine devraient se concentrer sur l'optimisation de l'assurance maladie intégrée rurale‐urbaine en élargissant les avantages sociaux actuels et en renforçant les efforts de lutte contre la pauvreté.